Dynamics of civil structures, volume 2 proceedings of the 33rd IMAC, a conference and exposition on structural dynamics, 2015 - International Modal Analysis Conference Orlando, Fla.) 2015; Caicedo, J. M.; Pakzad, Shamim; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
Dynamics of Civil Structures, Volume 2. Proceedings of the 33rd IMAC, , A Conference and Exposition on Balancing Simulation and Testing, 2015, the second volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: Modal Parameter Identification Dynamic Testing of Civil Structures Human Induced Vibrations of Civil Structures Correlation & Updating Operational Modal Analysis Damage Detection of Structures Bridge Structures Damage Detection Models Experimental Techniques for Civil Structures.
Electronic reproduction.
Keywords: Structural dynamics -- Congresses; Electronic books